Roll Amplification of Solid Rocket Motor in LAPAN Sounding Rocket - Sudiana, O.; Teofilatto, P. (BRIN Publishing, 2020)
Sounding rockets have been used for scientific research and implemented in meteorological and upper atmosphere studies since the late 1950s. Sounding rockets are sub-orbital carriers that follow a parabolic trajectory from launch to landing. Supporting the roadmap of Satellite Launch Vehicle development, LAPAN had launch The Sounding Rocket Program.A sensitive amplification from the production of an unpredicted roll rate was detected during the boost of the sounding rocket, despite of the tail wings in cruciform configuration at last flight test. One of this phenomenon can be influenced by the flow field of the combustion chamber during boosting time.The basic idea of this research is to model the roll amplification effect as a swirling motion of portion of exhaust gas that participate to the rotation dynamics of the rocket rather than to exit immediately flow the combustion chamber. Available flight data where is obtained from last flight test presented. It is shown the presence of a significant roll amplification when solid rocket motor is used during burning time. The result has a good agreement to presence of a portion of exhaust gas influence an unpredicted roll amplification.